2020
DOI: 10.3390/jzbg1010001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Daily Activity of Two Zoo-Housed Grizzly Bears (Ursus arctos horribilis)

Abstract: Captive grizzly bears, like their wild counterparts, engage in considerable variability in their seasonal and daily activity. We documented the year-long activity of two grizzly bears located at the Woodland Park Zoo in Seattle, Washington. We found that behaviors emerged in relation to month-to-month, seasonal, and time of day (hour-to-hour) observations, and events that occurred on exhibit, such as daily feedings. Seventeen behaviors split into seven classes of behavior were observed during their on-exhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…On warmer winter days, tropical bears were given access to their outdoor habitats, and on those days, their foraging rates were likely similar to other times of year. Other studies of bears in zoos have found variation in rates of foraging and stereotypy by season and visitor presence (Fernandez et al, 2020;Liu et al, 2017;Soriano et al, 2013), but we found that rates of foraging, stereotypy and social behaviors did not vary by season, crowd size, or daily attendance.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…On warmer winter days, tropical bears were given access to their outdoor habitats, and on those days, their foraging rates were likely similar to other times of year. Other studies of bears in zoos have found variation in rates of foraging and stereotypy by season and visitor presence (Fernandez et al, 2020;Liu et al, 2017;Soriano et al, 2013), but we found that rates of foraging, stereotypy and social behaviors did not vary by season, crowd size, or daily attendance.…”
Section: Discussioncontrasting
confidence: 76%
“…For example, a sloth bear housed at a zoo in India was observed to be more active in the winter (December-February) than the spring (March-May; Prajapati & Koli, 2020). Grizzly bears at Woodland Park Zoo in Seattle demonstrated higher pacing rates in the spring/summer (May-July) and higher activity levels in summer/fall (June-November; Fernandez et al, 2020). A black bear paced in different locations in the exhibit at different times of year, possibly in response to differing motivations between the seasons, such as mate-seeking behavior in spring/summer (May-July) and foraging in late summer/fall (August-November) (Carlstead & Seidensticker, 1991).…”
mentioning
confidence: 99%
“…Bears experiencing torpor are easily disturbed, and studies in the wild show that disturbances during torpor or ‘hibernation’ may result in metabolic derangements and activity for several days [ 43 ]. For zoo bears experiencing daily disturbances due to husbandry routines and visitor activity, achieving torpor may not be possible, even when bears demonstrate significant behavioural inactivity (e.g., [ 71 ]). Allowing bears to hibernate requires the provision of appropriate environmental provisions and a secluded and undisturbed environment [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The territory size for wild animals does not necessarily represent the amount of roaming they desire but can just be the amount of space needed to contain all the required resources for survival-sufficient sources of food, water and shelter [45]. A captive environment that provides all these needs within a smaller space may then be entirely sufficient-this will depend on details about the specific biology and behaviour of the animals of interest [46,47]. For example, some wide-ranging carnivores demonstrate stereotypes in captivity despite having their other needs provided, which suggests that for them, space itself is relevant [48].…”
Section: Understanding Freedom and Welfarementioning
confidence: 99%
“…As well as comparing ecology and behaviour, comparative welfare data could help form part of this analysis. There are also many research projects that look to compare the housing and husbandry conditions and behavioural and activity patterns between captive and wild species to try and identify welfare-relevant differences [46,47,80]. Veasey [77] provides an example of how an empirical analysis of the evolutionarily important cognitive and behavioural processes for a species can help determine their likely welfare in a captive setting and set priorities for improvement.…”
Section: The Need For Measurementmentioning
confidence: 99%